Peran Mediasi Green Innovation dan Accounting Capability pada Pengaruh Human Capital terhadap Kinerja Keuangan UMKM di Kota Surabaya - Khusnah, Hidayatul; Khoiriyah, Luluk (JURNAL AKUNTANSI DAN MANAJEMEN, 2025)
Micro, small, and medium enterprises (MSMEs) are one of the supporting sectors that contribute significantly to economic growth and are even considered a solution to improving the national economy. However, the development of MSMEs still faces obstacles in financial management. One way to address this problem is by increasing the use of payment gateways. Increasing the use of payment gateways helps MSMEs minimize financial management risks and improve financial performance. The purpose of this study is to empirically test the mediating role of green innovation and accounting capability on the financial performance of MSMEs with payment gateways as mediators. This study uses a quantitative descriptive approach with primary data and hypothesis testing using WarpPLS 7.0 software. The population in this study was all MSMEs in the city of Surabaya. The sampling method used was random sampling with 100 respondents. The test results show that only green innovation mediation plays a role in human capital and has a positive and significant effect on the financial performance of MSMEs. Green innovation has a positive and significant effect on the financial performance of MSMEs. Green innovation is able to mediate the influence of human capital on the financial performance of MSMEs.